STRATEGI PEMBENTUKAN BUDAYA TOLERANSI BERAGAMA MELALUI PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA KURIKULUM MERDEKA DI SEKOLAH PETRA BERKAT - Eko adi saputra; I Nyoman Subagia; I Gede Suwantana (JAPAM (Jurnal Pendidikan Agama), 2024)
Abstract The diversity of Indonesian society is a broad characteristic of the Indonesian nation which is characterized by the fact that there is social unity based on ethnic, religious, customary and regional differences. The diversity that exists in Indonesia should be a cause for the nation to grow closer to accept each other and make it a difference and dispute. On the one hand, religious pluralism is a source of cultural wealth and provides benefits for the Indonesian people because it can be used as a very rich source of inspiration for the democratic process in Indonesia. However, in the diversity of society in terms of religion, this constitutes social vulnerability if the development of religious life is not well organized, several problems often occur in Indonesia, from damage to places of worship, dissolution to murder, this means that special guidance and maturation must be carried out from an early age. from school. Based on this description, the researcher will focus on discussing: What are the Strategy Forms for Forming a Culture of Religious Tolerance Through Hindu Religious Education and Character Education in the Merdeka Curriculum at Petra Berkat School, The results of research using qualitative research methods will show that as follows: strategies for forming a culture of religious tolerance in Hindu religious education and character, there are several strategies such as, Application of tolerance values ​​in Hindu religion, empowerment of the school environment, multiculturalism, Implementation of the Tri sandya, Implementation of fast pasraman, Delivery of Hindu character education material in an inclusive manner and Monitoring and evaluation. Analysis of the strategy for establishing a culture of religious tolerance in the independent curriculum at the Petrathanks school is expected to strengthen the character of Hindu tolerance and also serve as a long-standing proposal for learning Hindu religious education in accordance with the Pancasila learning profile as a hope for student character.